HERANÇAS E APRENDIZAGENS NA TRANSMISSÃO DA ORDEM POLÍTICA BRASILEIRA (1945-2002) - Canedo, Letícia Bicalho (Cadernos CERU, 2004)
Positions of power in Brazil are increasingly occupied by individuals with international experience at prestigious schools and by those who have built their carriers with the benefit of knowledge obtained in international market. To understand the effects of this phenomenon on competition in a democratic context, this paper explores biographic data for 34 Brazilian politicians who held important elected positions in the central government (Congress and the Executive) during two key periods of restructuring in Brazilian politics (1945/1964 and 1984/2002). The paper analyses the social resources and types of academic knowledge that these politicians used to maintain and advance their careers. The politicians are evaluated in the context of the advantageous and unequal opportunities that they benefited from at the beginning of their carries and which contributed to their success and staying power in the unstable field of politics.